Privacy‐preserving framework for geosocial applications. Issue 11 (31st August 2013) - Malina, Lukas; Hajny, Jan
ABSTRACT The paper deals with user privacy in geosocial applications. Geosocial applications have become very popular but can misuse user's private data and location. We propose a novel solution that prevents tracking and protects against personal identity and location being misused by external attackers or service providers. The proposed framework provides security and privacy protection for geosocial applications that provide, for example, information sharing, geotagging, and monitoring of people without revealing their identity to unauthorized persons, including the service provider. Unlike current security solutions in geosocial services, our novel framework uses advanced cryptography to secure user privacy. This protection is provided by advanced group signatures ensuring data integrity, authenticity, non‐repudiation, and strong privacy protection. The paper outputs a detailed cryptographic scheme for the protection of privacy in geosocial services and its security analysis. The proposed scheme has also been implemented, and the performance results are outlined in the paper. Copyright © 2013 John Wiley & Sons, Ltd.